MIGRASI PENDUDUK DAN IMPLIKASINYA TERHADAP HANKAM DI WILAYAH PERBATASAN KALBAR-SERAWAK, MALAYSIA - Saru Arifin (Faculty of Law, Universitas Diponegoro, 2011)
The existence of the border society is part of the indicators of the state sovereignty. In the last 15years, the amount of the border society in West Kalimantan decreased. This is because of some of them are migrate to Sarawak. The border society migration was conducted through some ways, such as; married, birth, andasa labour. Among these migration patterns, a married and birth are most favourable. Looked from its region, the closest distance to Sarawak are the most migration supplier. And also the lost of economic region tends to supply the migration such as Sanggau, Ketunga Hulu, Aruk and some from Kapuas Huiu. By decreasing the amount of border society, it will influence to the border security. Because they most understand the border sign, illegal streets across the border while the ability of government to prepare army for guarding border is not comparable with the long of border which is reach 2004 km in lengt. Kata kunci :Migrasi, Penduduk Perbatasan, Pertahanan dan Keamanan